Land cover and NDBI analysis to map built up area in Iskandar Malaysia - yazrin, yassin; Jamallulail, Abdullah; Hj. Mohd. Noor, Norzailawati; Mariney, Mohd Yusof (IOP Publishing Ltd, 2020)
The growth of Iskandar Malaysia as a regional development corridor is inescapable large and rapid. The study area has been transformed from predominantly agricultural and forest land prior to 1990s into the second largest and third most urbanized area in peninsular Malaysia. The aim of this paper is to map Iskandar land cover change from 1991 to 2019 using sequential Landsat multi-spectral images with Normalized Difference Building Index (NDBI) analysis to assess spatio-temporal urban built up and its pattern. Accuracy assessment of kappa coefficient is used to measure the accuracy of classification. Research has proved a significant rapid land cover change and a vast transformation of agricultural and forest land into low density urbanized area scattered in Iskandar. A rapid land cover change of regional development corridor has significant influence on urban expansion especially to their periphery.